Sistematisasi Praktik Penghindaran Pajak di Perusahaan Pertambangan Sektor Minyak, Gas, dan Batu Bara - Ayu Wulansari; Rochmad Bayu Utomo (PT Bone Jaya Kreatif, 2023)
Tax revenue is utilized to finance state needs like education, security, infrastructure development, and people's welfare. However, achieving the tax revenue target is not always possible due to taxpayers engaging in tax avoidance. This study aims to assess the effectiveness of reducing tax avoidance by considering variables such as transfer pricing, return on assets, leverage, and fiscal loss compensation. The research utilizes positive accounting theory and the political cost hypothesis. The research population comprises oil, gas, and coal subsector mining companies listed on the IDX from 2020 to 2021. From this population, a total of 34 samples were chosen utilizing the purposeful sampling technique. The research method used in this study is quantitative, and the data was analyzed using the SPSS Version 29 software, employing the descriptive statistics methodology, classical assumption testing, multiple linear regression analysis, and hypothesis testing. The findings indicate that transfer pricing, return on assets, leverage, and fiscal loss compensation do not exert any influence on tax avoidance. This implies that these variables have no bearing on the decision-making process of companies when it comes to engaging in tax avoidance practices. Thus, it is essential to carefully consider the evaluation of policies and methods employed by companies in order to mitigate instances of tax avoidance